Doctors' adherence to guidelines recommendations and glycaemic control in diabetic patients in Quetta, Pakistan: Findings from an observational study - Saher, Tabassum; Al-Worafi, Yaser Mohammed; Iqbal, Muhammad Nouman; Wahid, Abdul; Iqbal, Qaiser; Khan, Asad; Atif, Muhammad; Ahmad, Nafees (Frontiers in Medicine, 2022)
Background Poor control of diabetes mellitus (DM) is partly attributed to doctors’ poor adherence to guidelines. Objective To evaluate doctors’ adherence to pharmacotherapeutic recommendations of DM management guidelines and factors associated with guidelines adherence and glycaemic control. Methods This prospective observational study included 30 doctors who were treating DM patients in their private clinics in Quetta, Pakistan. On visit 1, a total of 600 prescriptions written by 30 enrolled doctors (20 patients per doctor) were noted along with patients’ sociodemographic and clinical characteristics. American Diabetes Association guidelines was used as a reference. The prescriptions noted were judged for guidelines compliance. Of 600 enrolled patients, 450 patients (15 patients per doctor) were followed for one more visit and included in final analysis. Glycated haemoglobin (HbA1c) level noted one visit 2 was related with the respective prescription on visit 1. Data were analysed by SPSS (version 23). A p-value <0.05 was considered statistically significant. Results Patients received a median of two antidiabetic drugs (range: 1-5). A total of 73.1% patients were on polytherapy. Metformin was the most frequently prescribed (88.4%) antidiabetic followed by gliptins (46.2%). A total of 41.6% prescriptions were judged guidelines compliant. In multivariate binary logistic regressions (MVBLR) analysis, chronic kidney disease (CKD) (OR=0.422) and polytherapy (OR=0.367) had statistically significant negative associations (p-value <0.05) with guidelines’ compliant prescriptions. The group of doctors comprised of specialists and consultants wrote significantly (p-value=0.004) high number of guidelines adherent prescriptions (mean rank=20.25) than the group comprised of medical officers (mean rank=11.34). On visit 2, only 39.5% patients were on goal glycemic levels. In MVBLR analysis, suffering from dyslipidemia (OR=0.134) and CKD (OR=0.111), receiving sulfonylurea (OR=0.156) and guidelines’ compliant prescription (OR=4.195) were significantly (p-value <0.05) associated with glycemic control. Conclusion Although guidelines compliant prescriptions produced better glycemic control, but doctors’ adherence to guidelines and glycemic control were poor. Polytherapy and CKD emerged as risk factors for guidelines divergent prescriptions. Dyslipidemia, CKD and reception of sulfonylureas had negative association with glycemic control.